PROBLEMATIKA DAN STRATEGI IKRAR WAKAF MASJID DI INDONESIA - Rizki, Marisa; Yusuf, Suhairi; Hilal, Syamsul (STMIK Pringsewu, 2025)
Mosque waqf plays a strategic role in the social and spiritual development of Muslim communities in Indonesia. However, the implementation of mosque waqf pledges still faces various obstacles, such as low legality, waqf literacy, and suboptimal asset management. This study aims to analyze the problems and strategies of mosque waqf pledges in Indonesia through a qualitative case study approach. Data were collected through in-depth interviews, observation, and document analysis involving mosque administrators, nazirs, and KUA officials. The research findings show that the main obstacles in the waqf pledge process include low understanding of legal procedures, administrative complexity, and lack of public awareness. The research also identified several effective strategies, such as strengthening the role of the KUA, community education, and simplification of procedures. The implications of this research emphasize the need for improved policies and practical guidelines so that legal certainty and optimal management of mosque waqf assets in Indonesia can be ensured.